Overview on housing situation in Germany after First Word War with focus on activity of the GEHAG housing society in Berlin - Trammer, Hubert (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
After the First World War many reasons caused the increase of the scale of the problem of the bad housing conditions. This text presents the overview of the solutions, from the field of architecture and town planning as well as from the field of law and economy, created in Germany as an answer for the housing problem. The circumstances connected with them are also presented. There is a more detailed presentation of the activity of the biggest german association acting in the field of erecting housing assemblies – the GEHAG society (Gemeinnützige Heimsstätten- Aktiengesellschaft = Join-Stock Society for Social Settlements).